GAMBARAN PENGETAHUAN IBU TENTANG PEMBELAJARAN SECARA DARING PADA SISWA SEKOLAH DASAR DIMANA PANDEMI COVID -19 Di DESA RIMBA JAYA KEC.TAPUNG HULU KAMPAR TAHUN 2021 - ANDALIA ROZA; M KHOIRUDIN; LORA MARLITA (Jurnal Ilmu Keperawatan, 2021)
Online learning is one of the policies that the Indonesian government has had to take as an effort to break the chain of spreading Covid-19 in the community, especially in the school environment. This policy forces a change in learning from face-to-face between teachers and students to online/online-based learning. The research objective was to describe the knowledge of mothers about online learning. This research is a quantitative study with a descriptive design, the population in this study was 200 women in the village of Hutan Jaya. The sample was 134 mothers. The sampling technique was total purpsive sampling. The research instrument used a questionnaire with 15 questions. The results of statistical tests showed that the mother's knowledge was in the good category, namely 106 people (79.1%). Researcher suggestions for mothers to be able to further increase their knowledge about online learning during the pandemic so that they can help children in online learning